The Effectionces Of Visual Image In The Development Of Language Skills Of The Learner. - وداد عباد (International Journal of Social Communication, 2018)
Because sensory experiences are the basis of our knowledge of the world around us and others cannot be or aware of something, and the aware visual means of education can provide learners with such experiences necessary for learning, so that the process of education concerned with the use of practical means – in addition to verbal methods - in teaching, on one of these educational means represented in the visual image to see if there is an impact on the educational process of learning.